2D:4D biomarker reliability and validity in a within-subject pregnancy-childhood-adolescence cohort - Eichler, Anna; Kaufmann, Franziska; Titzmann, Adriana; Fasching, Peter; Beckmann, Matthias; Gerlach, Jennifer; Kratz, Oliver; Moll, Gunther; Buchholz, Verena Nadine; Kornhuber, Johannes; Lenz, Bernd (Early Human Development, 2023)
Background: A lot of studies use the second-to-fourth digit length ratio (2D:4D) as a biomarker for intrauterine androgen load to predict behavioral and mental health problems. Thus, knowledge of 2D:4D's metric properties, namely reliability and validity, is essential. Method: 2D:4D handscans were available from 149 adolescents (M = 13.32 years, SD = 0.35) and their mothers. For 88 adolescents, there were also primary-school age handscans (M = 7.87 years, SD = 0.68). Prenatal risks for the 1st to 3rd trimesters were recorded during the 3rd trimester of pregnancy (alcohol exposition: meconium biomarker and maternal self-report; nicotine exposition: maternal self-report; maternal depressive symptoms and subjective stress: questionnaires). Results: The 2D:4D ratio was highly stable from childhood to early adolescence. However, both developmental and sex effects were present: The 2D:4D ratio increased with age and was higher in adolescent girls vs. boys. Significant 2D:4D mother-child associations were found for girls. Significant main effects could be found for the prenatal risk factors alcohol (self-report) and nicotine consumption. Conclusion: In line with earlier studies, the 2D:4D biomarker proved to be an inter-individually stable measure with an intra-individual increase from childhood to early adolescence. Sex differences in adolescence and associations with maternal prenatal health behaviour underline the validity of the biomarker. Findings on heritability emphasize the importance of interpreting 2D:4D results in a sex-specific manner.
CRIS-Team Scopus Importer:2023-04-28
Keywords: 2D:4D ratio; Alcohol; Androgen load; Biomarker; Construct validity; Heritability; Nicotine; Pregnancy risk; Prenatal; Retest reliability; Stability; Testosterone exposure

A 10-Year-Old Girl’s Dysfunctional ‘Self-Help’ in ADHD: Suppression of Hyperkinetic Symptoms via Self-Induced Weight Loss in the Context of Anorexia Nervosa—A Case Report - Mestermann, Stefan; Stonawski, Valeska; Böhm, Lea; Kratz, Oliver; Moll, Gunther; Horndasch, Stefanie (Children, 2023)
Anorexia Nervosa (AN) and Attention Deficit Hyperactivity Disorder (ADHD) are frequent mental disorders in child and adolescent psychiatry. Comorbidity of these disorders is, however, rare among minors. Thus, little is known about their mutual impact on illness development as well as diagnostic and therapeutic influencing factors. We report the case of a 10-year old girl with AN and massive underweight. At the age of 5, ADHD had been diagnosed. Application of ADHD-specific medication had been refused by her caregiver. As of 3rd grade, hyperkinetic symptoms were significantly reduced, which was later linked to beginning AN-induced weight loss. At inpatient admission, no clinically relevant ADHD-related symptoms were present. Accompanying weight gain, rather ‘sudden’ appearance of attention difficulties, motoric hyperactivity and impulsivity were reported, widely impairing our patient’s schoolwork and further daily life. Methylphenidate medication showed good clinical response and tolerability. We hypothesize that the former massive underweight had suppressed ADHD-specific behaviour. AN with significant weight loss could possibly mask hyperkinetic symptoms in children. Thus, sufficient clinical diagnostics and intense monitoring during ED treatment are required. Physicians and therapists should be sensitized for interactions in the joint occurrence of these mental disorders among minors.
CRIS-Team Scopus Importer:2023-10-06
Keywords: ADHD; anorexia nervosa; child and adolescent psychiatry; comorbidity; mental health; methylphenidate; weight loss

Becoming a Teenager after Early Surgical Ventricular Septal Defect (VSD) Repair: Longitudinal Biopsychological Data on Mental Health and Maternal Involvement - Lang, Laura; Gerlach, Jennifer; Plank, Anne-Christine; Purbojo, Ariawan; Cesnjevar, Robert; Kratz, Oliver; Moll, Gunther; Eichler, Anna (Journal of Clinical Medicine, 2022)
Beside somatic strains of congenital heart diseases (CHD), affected children often show developmental impairments in the long term. Ventricular septal defect (VSD) is the most common congenital heart defect and early surgical repair is associated with positive somatic outcomes. However, psychological adjustment is of lifelong relevance. We investigated 24 children with a surgically-corrected isolated VSD and their mothers from primary school (6–9 years) to adolescence (10–14 years) and compared them to controls. Both times, mothers reported child internalizing/externalizing problems, mothers and children rated child quality of life, and children performed neurodevelopmental tests. Adolescents also rated internalizing/externalizing problems themselves, and their hair cortisol levels were analyzed. Maternal anxiety and proactive parenting behavior were considered as moderators. Results revealed no group differences in child neurodevelopment (language, cognition), externalizing problems, and cortisol levels at any time. In reports from mothers, internalizing problems (depression, anxiety) were elevated in children with a VSD at both times—when mothers reported anxiety symptoms themselves. In adolescent reports, VSD patients’ quality of life was increased and internalizing problems were decreased—proactive parenting behavior went along with decreased symptoms in VSD-affected adolescents and with increased symptoms in controls. The findings pronounce the crucial role of parenting behavior and the influence of maternal anxieties on child mental health after surgical VSD repair and might highlight the need for parent-centered interventions.
CRIS-Team Scopus Importer:2022-12-23
Keywords: adolescence; child development; congenital heart disease; cortisol; longitudinal study; mental health; psychological adjustment; quality of life; stress; ventricular septal defect

Early intervention for adolescents with anorexia nervosa: Pilot evaluation of an outpatient group therapy prior to inpatient treatment - Stonawski, Valeska; Stehbach, Christiane; Bauer, Marlen; Wangler, Susanne; Moll, Gunther; Horndasch, Stefanie; Kratz, Oliver (European Eating Disorders Review, 2024)
Objective: An increasing demand for inpatient treatment for adolescents with anorexia nervosa (AN) during and after the Covid-19 pandemic contrasts with limited capacity and long waiting times. The current pilot study evaluated an outpatient group therapy (GT) as early intervention for adolescents with AN prior to inpatient treatment. Methods: Seventeen female adolescents who participated at the GT (intervention group, INT) were compared to 16 adolescents without GT (treatment-as-usual, TAU). BMI, eating disorder psychopathology and motivation of change (MoC) were assessed at three timepoints. Results: Comparing pre- versus post- group participation, we identified a significant increase of MoC and a trend towards a decreased AN-specific psychopathology. Comparing INT with TAU adolescents, we found a significant lower AN psychopathology at inpatient admission for the INT group and a trend for different BMI courses: While the BMI of the TAU group decreased during waiting time, the INT group did not show a decrease during GT resulting in a higher BMI at admission. Conclusions: Results of the current pilot study suggest positive effects of an early outpatient intervention in a group setting for adolescents with AN prior to inpatient treatment. Further research with larger sample sizes is necessary to validate the current pilot results.
CRIS-Team Scopus Importer:2024-08-23
Keywords: adolescents; anorexia nervosa; early intervention; group therapy; motivation of change

Effects of an App-Based Mindfulness Intervention during Pregnancy on the Infant’s Prenatal Androgen Exposure: A Randomized Controlled Pilot Trial - Siegmann, Eva-Maria; Eichler, Anna; Buchholz, Verena Nadine; Gerlach, Jennifer; Pontones, Constanza; Titzmann, Adriana; Arnaud, Nicolas; Consortium, Imac Mind; Mühle, Christiane; Beckmann, Matthias; Fasching, Peter; Kratz, Oliver; et al. (Journal of Clinical Medicine, 2023)
Prenatal androgen exposure modulates the development of the brain, with lasting effects on its function and behavior over the infant’s life span. Environmental factors during pregnancy, in particular maternal stress, have been shown to influence the androgen load of the unborn child. We here addressed the research gap on whether a mindfulness intervention or a pregnancy education administered to pregnant women more affects the androgen exposure of the unborn child (quantified by the proxies of second-to-fourth digit length ratio (2D:4D) and anogenital distance assessed one year after delivery and at delivery, respectively). Moreover, we tested the mindfulness intervention’s effects on maternal perceived stress, anxiety, depressiveness, and mindfulness. Pregnant women (gestation weeks 8–14) were randomized to a 15-week app-based mindfulness-oriented intervention (N = 72) or a pregnancy education intervention (control condition; N = 74). The mindfulness-oriented group did not significantly differ from the pregnancy education group in infants’ 2D:4D or anogenital distance (partial η2 ≤ 0.01) or in maternal stress, anxiety, depressiveness, or mindfulness. However, the descriptive results indicate that across pregnancy, stress and anxiety decreased and mindfulness increased in both groups. Overall, this study did not show that the mindfulness intervention (relative to the pregnancy education) reduced the prenatal androgen exposure of the unborn children or improved the maternal outcomes significantly.
CRIS-Team Scopus Importer:2023-10-20
Keywords: digit ratio; mindfulness; prenatal programming

Effects of prenatal alcohol exposition on cognitive outcomes in childhood and youth: a longitudinal analysis based on meconium ethyl glucuronide. - Roetner, Jakob; Van Doren, Jessica; Maschke, Janina; Kulke, Louisa; Pontones, Constanza; Fasching, Peter A.; Beckmann, Matthias W.; Lenz, Bernd; Kratz, Oliver; Moll, Gunther; Kornhuber, Johannes; Eichler, Anna (European archives of psychiatry and clinical neuroscience, 2024)
BACKGROUND: Prenatal alcohol exposure (PAE) has been linked to severe, adverse child outcomes. However, little is known regarding subclinical outcomes of low/moderate PAE and its longitudinal consequences, especially regarding neurophysiological and neurocognitive development. A newborn biomarker of PAE, meconium ethyl glucuronide (EtG), has been shown to predict cognitive impairments in primary-school-aged children. The current study investigated the ongoing effects of subclinical PAE in adolescence. METHODS: A sample of n = 96 mother-child dyads of the FRAMES/FRANCES cohort were classified into PAE/no PAE using EtG with a 10 ng/g cutoff. Mothers were recruited during pregnancy and children were assessed during primary-school age (M = 7.57, SD = 0.65, range: 6.00-9.92 years) and adolescence (M = 13.26, SD = 0.31, range: 12.79-14.20 years) on three levels: clinical (ADHD rating), neuropsychological (IQ score and performance in a go/nogo task), and neurophysiological (analysis of P3 event-related potentials (ERP) during said go/nogo task). Developmental outcomes and courses following PAE were assessed using rmANCOVAs, controlling for relevant confounders (socioeconomic status (SES), birth weight, and maternal psychopathology). RESULTS: Neurophysiological impairments emerged for exposed children in the form of diminished attentional resource recruiting in childhood and adolescence (reduced go-P3 amplitudes) with no differences in performance. Neuropsychological testing showed a reduced IQ score for both time points with dose-dependent effects in childhood. Clinical ADHD symptoms were not significantly affected. CONCLUSION: Subclinical PAE, as determined by meconium EtG, has negative developmental consequences on cognitive function that persist from childhood to adolescence. These findings suggest that there is no safe limit for alcohol consumption during pregnancy and that more thorough screening of alcohol consumption during pregnancy is necessary for early identification and treatment of at-risk children.
EVALuna2:538816

Effects of the COVID-19 Restrictions on Eating Behaviour and Eating Disorder Symptomology in Female Adolescents - Muth, Lois; Leven, Karl-Heinz; Moll, Gunther; Kratz, Oliver; Horndasch, Stefanie (International Journal of Environmental Research and Public Health, 2022)
Confinement due to the COVID-19 pandemic imposes a burden on adolescents worldwide and may seriously impact patients with an eating disorder (ED). The current FRanconian Anorexia Nervosa during COVID-19 (FRANCO) study explored (1) perceived change of depressive and ED symptomology during lockdown, (2) the role of social media, and (3) coping strategies of anorexia nervosa (AN) patients and clinical as well as healthy comparison groups. From June 2021 to September 2021, 222 female adolescents (19 with AN, 20 with depression, 45 with a self-reported psychiatric disorder (SRPD), and 138 controls) aged 11.2 to 18.9 years completed a one-time anonymous survey retrospectively reporting back on ED and depressive symptomology before and during the pandemic, the impact of social media, and coping strategies. A reduced quality of life (QoL) due to confinement was observed in almost half of female adolescents. All groups reported a significant perceived increase of disordered eating, overeating, anxiety, and depressive symptoms and emotion-regulation problems. In AN patients, significantly higher percentual deterioration of disordered eating and anxiety and depressive symptoms was found. For controls, a younger age and higher susceptibility of the sociocultural body image significantly correlated with increased disordered eating. Large-scale media literacy interventions are recommended.
CRIS-Team Scopus Importer:2022-08-12
Keywords: adolescents; anorexia nervosa; COVID-19 pandemic; depression

Heart Rate as a Correlate for the Emotional Processing of Body Stimuli in Anorexia Nervosa - Horndasch, Stefanie; Sharon, Elisabeth; Eichler, Anna; Graap, Holmer; Moll, Gunther; Kratz, Oliver (Behavioral Sciences, 2023)
In anorexia nervosa, aberrant emotional reactions toward body stimuli have been discussed. We investigated heart rate as a physiological marker when viewing body stimuli and hypothesized altered HR reactions toward those highly significant and emotional stimuli in anorexia nervosa. In total, 37 anorexia nervosa patients and 43 control participants viewed pictures of women of five different weight categories, while their cardiac activity was recorded. R-R intervals following picture onset were determined, and means were calculated for three distinct time periods. The overall change in HR relative to baseline across all picture categories was greater in the patient group than in the control group (significant effect of “group”, p = 0.002, partial η2 = 0.120). A significant decrease in HR 2 to 8 s after picture presentation was found for pictures of women of extreme weight in both participant groups (significant “category ∗ time segment interaction”, p = 0.01, partial η2 = 0.037) and correlated with scores of sociocultural attitudes toward the appearance for the extremely underweight category (r = −0.33, p = 0.005). Therefore, differential HR reactions for anorexia nervosa patients and control participants were found for body stimuli in general. The highest HR decelerations in response to pictures of strongly underweight and overweight women may reflect emotional processes such as anxiety due to social comparison.
CRIS-Team Scopus Importer:2023-04-07
Keywords: adolescents; anorexia nervosa; body stimuli; heart rate

Processing of food stimuli in anorexia nervosa: An ERP-study comparing adolescents and adults - Stonawski, Valeska; Mai-Lippold, Sandra A.; Graap, Holmer; Moll, Gunther; Kratz, Oliver; Van Doren, Jessica; Horndasch, Stefanie (European Eating Disorders Review, 2023)
Background: Anorexia nervosa (AN) is associated with altered processing of disorder-relevant stimuli. Event-related potentials (ERP) – such as the Late Positive Potential (LPP) – give information about the underlying mechanisms of central nervous stimulus processing. Methods: Patients with AN (22 adolescents, 23 adults) and healthy controls (HCs; 17 adolescents, 24 adults) were included. Neutral, low, and high calorie food-images were rated for valence and arousal; EEG activity was recorded and LPPs (early: 350–700 ms; late: 800–1200 ms) were extracted. Effects of patient status, age group, and stimulus category were analyzed via mixed 2 × 2 × 3-AN(C)OVAs. Results: Patients with AN rated high calorie stimuli lower in valence and higher in arousal than HCs. Controlling for hunger, food stimuli elicited higher early LPPs than neutral ones in patients and HCs. For the late LPP, patients with AN showed larger amplitudes. Conclusion: Results suggest a highly automatic attentional bias towards low-calorie foods. Patients with AN seem to have more intense cognitive processing independent of stimulus material. More research is needed to validate and clarify differences between early and late LPP measures as well as the operationalization and relevance of hunger status.
CRIS-Team Scopus Importer:2023-10-27
Keywords: adulthood; anorexia nervosa; childhood; food; LPP

The Benefit of a Retrospective Pregnancy Anamnesis in Child and Adolescent Psychiatry: The Reliability of Maternal Self-Report during Childhood Development - Mestermann, Stefan; Fasching, Peter; Beckmann, Matthias; Gerlach, Jennifer; Kratz, Oliver; Moll, Gunther; Kornhuber, Johannes; Eichler, Anna (Children, 2023)
Pregnancy anamnesis is a crucial part of child and adolescent psychiatry diagnostics. In previous works, the reliability of retrospective maternal self-report on perinatal characteristics was heterogeneous. This prospective longitudinal study aimed to evaluate women’s recall of prenatal events in a within-subject design. A sample of 241 women gave a self-report on prenatal alcohol, smoking, partnership quality, pregnancy satisfaction, and obstetric complications during the 3rd trimester (t0), childhood (t1, 6–10 y), and adolescence (t2, 12–14 y). The intra-individual agreement was examined. The t0–t1–(t2) agreement was poor to substantial; this was highest for smoking and worst for obstetric complications, followed by alcohol (Fleiss’ κ = 0.719 to −0.051). There were significant t0–t1–(t2) differences for all pregnancy variables (p < 0.017), except for 3rd trimester satisfaction (p = 0.256). For alcohol (t0 25.8%, t1 17.4%, t2 41.0%) and smoking (t0 11.9%, t1 16.4%, t2 22.6%), the highest self-reported rates were found during adolescence. During childhood, fewer obstetric complications (t0 84.9%, t1 42.2%) and worse partnerships were reported (t0 M = 8.86, t1 M = 7.89). Thought to be due to social stigmata and memory effects, pregnancy self-reports cannot be precisely reproduced. Creating a respectful and trusting atmosphere is essential for mothers to give honest self-reports that are in the best interest of their children.
CRIS-Team Scopus Importer:2023-06-30
Keywords: alcohol; partnership; pregnancy; pregnancy satisfaction; prenatal; retrospective; risk perceptions; self-report; smoking

The Father’s Part: Influences of Paternal Psychopathology and Parenting Behavior on Child and Adolescent Well-Being - Mestermann, Stefan; Arndt, Marie; Fasching, Peter; Beckmann, Matthias; Kratz, Oliver; Moll, Gunther; Kornhuber, Johannes; Eichler, Anna (Healthcare, 2023)
Family influences on child quality of life (QoL) are increasingly understood. Parenting behavior and parent individual psychopathology are among the established predictors of offspring mental health. However, literature often addresses these factors as ‘parental’, lacking further gender-specific differentiation while predominantly studying maternal aspects. Social and biological fathers are still underrepresented in family research. The aim of this study was to analyze paternal contributions to child well-being. A total of 197 father/mother-dyads gave a standardized self-report on parenting behavior and their own psychopathology at child primary school age (t1; 6–10 y). Ratings were compared mutually and associated with child self-rated QoL at t1 and adolescence (t2; 12–14 y). Fathers and mothers differed in psychopathology and most parenting behavior dimensions (positive parenting, involvement, responsible parenting, poor monitoring, and corporal punishment). Father psychopathology made a relevant predictive contribution to girls’ QoL at t2. Boys’ t1 QoL was significantly influenced by maternal parenting factors (positivity and corporal punishment). Compared to mothers, fathers are faced with different individual stressors; paternal parenting behavior is different, while fathers’ influences are significant, particularly for daughters. Father-addressed pre- and intervention programs in child psychotherapeutic treatment are of high relevance.
CRIS-Team Scopus Importer:2023-08-25
Keywords: child development; father; parent-child-relations; parental influence; parenting; parenting behavior; resilience